SOSOK TIMOTIUS WARSITO SEBAGAI PELUKIS ABSTRAK - Budi Waluyo (Universitas Mercu Buana, 2020)
Timothy Suwarsito, a dedicated self-taught painter. He was a hard worker, both as a painter, as an educator and as a whole person. His freedom of thought, imagination, and work is his attitude. Creativity is a word that must be lived, cultivated and put together with him, he hopes to be a creative person. So he diligently searched. He explored. By standing on earth living life, what is desired, is tried to be realized. Do not care about the fact that sometimes it is indeed bitter and for him, it is a challenge that must be faced and defeated. As a human being, he believes in his intuition (as reflected in his work). Within a few decades, he changed jobs not because he wanted to make a profit, but because he followed his conscience, his conscience that was often right, produced happiness. It turns out that life does have to choose. He chose to be an abstract painter and at the same time as an educator, guiding children, youth, and adults to paint.